A randomised, active- and placebo-controlled, three-period crossover trial to investigate short-term effects of the dipeptidyl peptidase-4 inhibitor linagliptin on macro- and microvascular endothelial function in type 2 diabetes. Issue 1 (December 2017) - Jax, Thomas; Stirban, Alin; Terjung, Arne; Esmaeili, Habib; Berk, Andreas; Thiemann, Sandra; Chilton, Robert; Eynatten, Maximilian; Marx, Nikolaus
Abstract Background Studies of dipeptidyl peptidase (DPP)-4 inhibitors report heterogeneous effects on endothelial function in patients with type 2 diabetes (T2D). This study assessed the effects of the DPP-4 inhibitor linagliptin versus the sulphonylurea glimepiride and placebo on measures of macro- and microvascular endothelial function in patients with T2D who represented a primary cardiovascular disease prevention population. Methods This crossover study randomised T2D patients (n = 42) with glycated haemoglobin (HbA1c) ≤7.5%, no diagnosed macro- or microvascular disease and on stable metformin background to linagliptin 5 mg qd, glimepiride 1–4 mg qd or placebo for 28 days. Fasting and postprandial macrovascular endothelial function, measured using brachial flow-mediated vasodilation, and microvascular function, measured using laser-Doppler on the dorsal thenar site of the right hand, were analysed after 28 days. Results Baseline mean (standard deviation) age, body mass index and HbA1c were 60.3 (6.0) years, 30.3 (3.0) kg/m2 and 7.41 (0.61)%, respectively. After 28 days, changes in fasting flow-mediated vasodilation were similar between the three study arms (treatment ratio, gMean [90% confidence interval]: linagliptin vs glimepiride, 0.884 [0.633–1.235]; linagliptin vs placebo, 0.884 [0.632–1.235]; glimepiride vs placebo, 1.000 [0.715–1.397];P = not significant for all comparisons). Similarly, no differences were seen in postprandial flow-mediated vasodilation. However, under fasting conditions, linagliptin significantly improved microvascular function as shown by a 34% increase in hyperaemia area (P = 0.045 vs glimepiride), a 34% increase in resting blow flow (P = 0.011 vs glimepiride, P = 0.003 vs placebo), and a 25% increase in peak blood flow (P = 0.009 vs glimepiride, P = 0.003 vs placebo). There were no significant differences between treatments in postprandial changes. Linagliptin had no effect on heart rate or blood pressure. Rates of overall adverse events with linagliptin, glimepiride and placebo were 27.5, 61.0 and 35.0%, respectively. Fewer hypoglycaemic events were seen with linagliptin (5.0%) and placebo (2.5%) than with glimepiride (39.0%). Conclusions Linagliptin had no effect on macrovascular function in T2D, but significantly improved microvascular function in the fasting state. Trial registration ClinicalTrials.gov identifier—NCT01703286; registered October 1, 2012